QUALITY ALGORITHMS OF DYNAMIC SYSTEMS IDENTIFICATION - Глазок, О. М. (Science-based technologies, 2013)
А regressive and an adaptive algorithms of parametric identification of dynamic systems which allow to conduct identification at the nominal modes of operation of the controlled object and satisfy the specified requirements to speed of fading of dynamic processes of identification are offered. The offered algorithms can be applied in the practice of aircraft design for processing the flight information records.